Implementing universal health coverage: how far can the law take us? - Ahmad, Nava Khorram (Riga Graduate School of Law, 2023)
In light of an increasingly interconnected world, health equity and the universality of health is of growing importance. The thesis examines the legal obligations of states in upholding the universality of healthcare, mainly through the provision of universal health coverage, in the EU, US, and the UK. The research looks at international, regional, and national frameworks, examining how these frameworks are implemented in practice and what limitations and challenges they present. The author's research reveals that the EU and the UK prioritize the right to health and universal healthcare coverage to ensure accessible healthcare without financial burden. Conversely, the US indirectly implements the right to health by establishing a high-quality healthcare system, but without universal health coverage, resulting in a lack of universal healthcare. The author attributes these differences to the EU and UK enshrining the right to health in their constitutions and laws, making healthcare universality a primary objective. Additionally, cultural ideologies in these regions have either facilitated or hindered universal health coverage implementation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Social welfare law; universal health coverage; right to health; The United States; The European Union; The United Kingdom